Sarcopenia, myosteatosis and inflammation are independent prognostic factors of SARS-CoV-2 pneumonia patients admitted to the ICU - Romain Chauvot de Beauchene; Bertrand Souweine; Benjamin Bonnet; Bertrand Evrard; Yves Boirie; Lucie Cassagnes; Claire Dupuis (Scientific Reports)
Abstract The aims of our study were to assess the correlations between sarcopenia and myosteatosis assessed by CT-scan at T4 and/or L3 levels and inflammation in critically ill COVID patients on ICU admission, and their respective prognostic value on day 90 death (D90-death). It is a retrospective monocentric study. Sarcopenia was defined by skeletal muscle cross sectional surface area (CSA) and myosteatosis by skeletal muscle density (SMD) at L3 and T4 levels. Inflammatory biomarkers were collected on ICU admission. Of the 239 patients, 74 died by D90; 66.6% get sarcopenia on ICU admission. CSA at T4 level was an independent risk factor for D90-death (1.66[1.03; 2.66]; p = 0.04), as were procalcitonin (2.03[1.2; 3.43]; p = 0.01) and IL-6 levels (1.56[0.96; 2.54]; p = 0.07). In addition, we found correlation factors of 0.79 (p < 0.01) between SMD at T4 and L3 levels, and a correlation factor of 0.64 (p < 0.01) between CSA at T4 and L3 levels.These results indicate a poorer prognosis following a decrease in muscle surface area, a decrease in density, and an increase in inflammatory biomarkers such as Il6. It also suggests that incorporating indices of sarcopenia with inflammatory biomarkers may improve prognostic accuracy.